2010
DOI: 10.1016/j.bcp.2009.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of oxime-bound fenamiphos-acetylcholinesterases: Reactivation involving flipping of the His447 ring to form a reactive Glu334–His447–oxime triad

Abstract: -Ping Pang, Fredrik Ekström. Crystal structures of oxime-bound fenamiphos-acetylcholinesterases: reactivation involving flipping of the His447 ring to form a reactive Glu334-His447-Oxime triad. Biochemical Pharmacology, Elsevier, 2009, 79 (3) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…1). Then, with Discovery Studio 3.0 software, we proceed to create homology models using the M. musculus AChE crystal structure PDB: 2WU3 model (Resolution=2.15 Å) (Hornberg et al 2010), as the better 3D experimental template (sequence identity= 91.2 % and similarity=92.7 %). The generated 3D model is present in Fig.…”
Section: Conception Of the 3d Structure Of R Norvegicus Achementioning
confidence: 99%
“…1). Then, with Discovery Studio 3.0 software, we proceed to create homology models using the M. musculus AChE crystal structure PDB: 2WU3 model (Resolution=2.15 Å) (Hornberg et al 2010), as the better 3D experimental template (sequence identity= 91.2 % and similarity=92.7 %). The generated 3D model is present in Fig.…”
Section: Conception Of the 3d Structure Of R Norvegicus Achementioning
confidence: 99%
“…We have previously suggested that His447 and a water molecule activate the oxime by a hydrogen transfer mechanism to generate a deprotonated species that is presumed to attack the phosphorus atom (6,29). This proposal has been challenged by kinetics data, which suggested that the oxime binds in its deprotonated form (30).…”
Section: Reactivation Kinetics Measurements Show the Importance Of Glmentioning
confidence: 99%
“…2. Mice AChE inhibited by fenamiphos (in magenta; whole enzyme -left; active siteright; 2wu3.pdb) (Hornberg 2010).…”
Section: Fig 1 Organophosphorus Insecticidesmentioning
confidence: 99%
“…sarin, soman, tabun, VX), but it is also known for some OP insecticides (e.g. dimethoate, fenamiphos) (Hornberg 2010). For the aging reasons, the acute OPP intoxication should be rapidly treated by causal drugs (oxime reactivators) (Bajgar 2007).…”
Section: Wwwintechopencommentioning
confidence: 99%